Open Educational Resources in Canada 2015 - McGreal, Rory; Anderson, Terry; Conrad, Dianne (International Review of Research in Open and Distributed Learning, 2015)
Canada’s important areas of expertise in open educational resources (OER) are beginning to be built upon or replicated more broadly in all education and training sectors. This paper provides an overview of the state of the art in OER initiatives and open higher education in general in Canada, providing insights into what is happening nationally and provincially. There are growing examples of OER initiatives from several Canadian institutions offering free courses to Canadians and international learners. National open education initiatives include the federal government's Open Data pilot project and the Council of Ministers of Education of Canada (CMEC) support for the Open Educational Resource Paris Declaration, as well as Creative Commons Canada. Regionally, the western provinces of British Columbia and Alberta are supporting OER as part of major open education initiatives.